PROBLEMATIC ASPECTS OF HEALTH-PRESERVING COMPETENCE DEVELOPMENT IN PRESCHOOL TEACHERS - Andriushchenko, Tetiana; Lokhvytska, Liubov; Martovytska, Nataliia; Sirenko, Alla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The article substantiates the problem of health-preserving competence development in teachers of preschool education: as an important task of the modern world, as a priority personal characteristic, as a component of professional training. The essence of the phenomenon of “health-preserving competence” is revealed, the following structural components are distinguished: emotional and motivational, cognitive and activity-centered. The goal of the research is to determine the conceptual foundations of the development of health-preserving competence in teachers of preschool education; data collection and processing of information to clarify problematic aspects of the phenomenon being under consideration. In the course of empirical research, the authors used the method of anonymous thematic survey (questionnaire) and its analysis. The research group consisted of: students of the 4th year of dual mode of study (who work on specialty) – 38 participants (group A); students of the 4th year of part-time mode of study who work on specialty (in preschool educational institutions) – 45 participants (group B) and students of advanced training courses – 53 participants (group C). The total number is 136 respondents. The conducted research proved that the respondents are aware of the main categories of health; are motivated and aware of the importance of health-preserving behavior, but are not sufficiently aware of modern health-preserving technologies. Therefore, the activity-centered component requires to be strengthened for the development of health-preserving competence in teachers of preschool educational institutions. Prospects for further scientific work will consist in the implementation to the system of higher education and advanced training courses for preschool teachers of the elective course “Formation of health-preserving competence in the subjects of the educational process” and determining the effectiveness of its implementation.